Low‐dose‐rate brachytherapy for the treatment of localised prostate cancer in men with a high risk of disease relapse. (8th May 2018) - Laing, Robert; Uribe, Jennifer; Uribe‐Lewis, Santiago; Money‐Kyrle, Julian; Perna, Carla; Chintzoglou, Stylianos; Khaksar, Sara; Langley, Stephen E.M.
Abstract : Objectives: To report clinical outcomes of 125 I low‐dose‐rate prostate brachytherapy (LDR‐PB) as monotherapy or combined with androgen‐deprivation therapy (ADT) and/or external beam radiotherapy (EBRT) in high‐risk localised prostate cancer. Patients and Methods: Analysis of clinical outcomes from a prospective cohort of patients treated with LDR‐PB alone or combined treatment in a single institution. Men with a high risk of disease relapse were identified by the National Institute for Health and Care Excellence (NICE) criteria or by the National Comprehensive Cancer Network (NCCN) criteria. Relapse‐free survival (RFS), overall survival (OS), prostate cancer‐specific survival (PCSS), and metastases‐free survival (MFS), were analysed together with patient‐reported symptom scores and physician‐reported adverse events. Results: The NICE and NCCN criteria identified 267 and 202 high‐risk patients, respectively. NICE‐defined patients had significantly lower pre‐treatment PSA levels, Gleason scores <7, and a greater proportion of patients who received LDR‐PB monotherapy. At 9 years after implantation RFS was 89% and 87% in the NICE and NCCN groups, respectively (log‐rank P = 0.637), and OS 93% and 94%, respectively (log‐rank P = 0.481). All of the survival estimates were similar between LDR‐PB monotherapy and combined therapies. Cox proportional hazards regression confirmed RFS was similar between the treatment types. Treatment‐related toxicity was also similar between the treatment methods. Conclusion: LDR‐PB is effective at controlling localised prostate cancer in patients with a high risk of disease relapse. As the present study was not randomised, it is not possible to define those patients who need the addition of ADT and/or EBRT. However, the NICE criteria appear suitable to define treatment options where patients could benefit from LDR‐PB as monotherapy or combined treatment. This choice should be discussed with the patient taking into account comorbidities and presence of multiple high‐risk factors.